Imperialism in the modern phase. Ed. by Baudhayan Chattopadyay (People's Publishing House, 1974)
1.Papers of the International Seminar on imperialism, independence and social transformation in the contemporary world. Organised by Indian Sponsoring Committee, World Peace Council and Afro-Asian People's Solidarity Organisation. [1974]. XII, 242 p. - With tabs.